СОВЕРШЕНСТВОВАНИЕ РАБОТЫ СТУДЕНТОВ В ИНТЕРНЕТ СЕТЯХ - Атоев, Э.Х. (SCIENCE and SOCIETY, 2020)
The article deals with the opinion about the formation of youth‘s culture of using the Internet, to protect the m- selves from the effects of negative information in their worldview, the ability to distinguish information that is poi- sonous to human thinking and to develop immunity within themselves to protect from negative information.